vv

13490 Reputation

20 Badges

9 years, 181 days

MaplePrimes Activity


These are answers submitted by vv

The idea is to expand in power series and then change the order of summation. After that, the limit will be simple.

restart;

f := k*t^k/(1-t^k); # without (1-t)^2

k*t^k/(1-t^k)

(1)

f := convert(eval(f, t^k=u), FPS, u) assuming k::posint

Sum(k*u^(n+1), n = 0 .. infinity)

(2)

f := (eval(%, u=t^k)) assuming k>0,t>0

Sum(k*(t^k)^(n+1), n = 0 .. infinity)

(3)

term := op(1,%)

k*(t^k)^(n+1)

(4)

F := Sum(sum((1-t)^2*term, k=1..infinity),n=0..infinity) assuming t>0,t<1;

Sum((t-1)^2*t^(n+1)/(t^(n+1)-1)^2, n = 0 .. infinity)

(5)

limit(F, t=1,left)

Sum(1/(n+1)^2, n = 0 .. infinity)

(6)

ans = value(%);

ans = (1/6)*Pi^2

(7)
 

 

Download lim_ser-vv.mw

Maple can guess the result:

s:=sum( arctan(2/n^2), n=1 .. infinity);
ans:=identify(evalf(s));
evalf[200](s - ans);  # check 200 digits, --> 0

                  

PS. Why don't you express the series in Maple, i.e.  sum( arctan(2/n^2), n=1 .. infinity) ?

PS2. Of course this is not a proof.  It is easy to obtain one in Maple, but only if the user knows it mathematically.
I omit it because you probably know it.

Maple cannot compute it, but it's easy with Stoltz-Cesaro theorem:

a:=n -> 2^n/n:
limit(a(n) / (a(n)-a(n-1)), n=infinity);

                    2

J:=Int(ln(x)*ln(1 - x), x = 0 .. 1);

Int(ln(x)*ln(1-x), x = 0 .. 1)

(1)

F2:=convert(ln(1-x), FPS);

Sum(-x^(n+1)/(n+1), n = 0 .. infinity)

(2)

J1:=Int(ln(x)*op(1,F2), x=0..1);

Int(-ln(x)*x^(n+1)/(n+1), x = 0 .. 1)

(3)

value(%) assuming n>=0; # by parts

1/((n+1)*(n+2)^2)

(4)

V1:=convert(%, parfrac);

-1/(n+2)+1/(n+1)-1/(n+2)^2

(5)

J = sum(V1, n=0..infinity);  # Easy to justify by dominated convergence

Int(ln(x)*ln(1-x), x = 0 .. 1) = 2-(1/6)*Pi^2

(6)


Download INT1-vv.mw

Try  (*.mw, not *.mpl):

interface(worksheetdir);

 

 1/(1 - x*y) = Sum( (x*y)^k, k=0 .. infinity );
Applying the double integral over (0,1)^2 implies (by monotone convergence):
 Int( 1/(1 - x*y), x=0..1, y=0..1 ) = Sum( 1/k^2, k =1 .. infinity );
==>  Int( 1/(1 - x*y), x=0..1, y=0..1 ) = Pi^2 / 6.

You have to use LinearAlgebra[Modular]:

restart
A:=Matrix(9,[
0,0,0,-1,1,-1,-1,0,0,
0,-1,0,1,-1,1,0,-1,-1,
0,0,-1,0,0,0,1,1,0,
0,1,0,-1,-1,1,-1,-1,0,
0,0,0,0,0,-1,1,0,-1,
0,0,0,0,0,-1,0,1,1,
0,0,1,-1,1,1,-1,-1,0,
0,0,0,0,0,1,1,-1,0,
0,0,0,0,0,0,0,0,0], datatype=integer[8]):
with(LinearAlgebra[Modular]):
Rank(3,A);
#                               7
B := Copy(3,A):
RowReduce(3,B,9,9,9,'det',0,'rank',0,0,true): B;

            

 

Edit. To obtain a basis for the nullspace explicitly, it is better to use:

with(LinearAlgebra[Modular]):
A1 := Copy(3,A):
r:=MatBasis(3, A1, 9, true): r,A1;
colonbasis, nullspacebasis:= A1[1..r, ..], A1[r+1.., ..];
colonbasis . nullspacebasis^+  mod 3; # check (==> 0 matrix)

OK, I'll take Z(t) = exp(int(y(u),u=0..t))

restart
eq1 := diff(x(t), t)-(1/6)*(6*x(t)^3*y(t)+(2*y(t)^2-2)*x(t)^2+3*y(t)*(z(t)-2)*x(t)-2*y(t)^2+2)*sqrt(3) = 0;
eq2 := diff(y(t), t)-(1/6)*(y(t)-1)*sqrt(3)*(y(t)+1)*(6*x(t)^2+2*y(t)*x(t)+3*z(t)-2) = 0;
eq3 := diff(z(t), t)-(1/3)*z(t)*sqrt(3)*(6*y(t)*x(t)^2+2*x(t)*y(t)^2+3*z(t)*y(t)-2*x(t)-3*y(t)) = 0;
eq4 := diff(s(t), t)-(1/3)*(y(t)-1)*sqrt(3)*(y(t)+1)*(6*x(t)^2+2*y(t)*x(t)+3*z(t)-2)*y(t) = 0;
eq5 := diff(Q(t), t)+sqrt(3)*((4/3-z(t)-2*x(t)^2)*y(t)+(2/3*(1-y(t)^2))*x(t))*Q(t)+2*((2/3)*y(t)+x(t))*P(t)/sqrt(3)-(2/3)*R(t) = 0;   
eq6 := diff(P(t), t)+(sqrt(3)*(1-z(t)-2*x(t)^2)*y(t)+2*(2-y(t)^2)*x(t)/sqrt(3))*P(t)+2*sqrt(3)*x(t)*Q(t)+(1/2)*R(t) = 0;       
eq7 := diff(R(t), t)-sqrt(3)*((3*x(t)^2+(3/2)*z(t)+4)*y(t)-(1/3*(1-3*y(t)^2))*x(t))*R(t)-z(t)*P(t) = 0;
eq8 := diff(T(t), t)-sqrt(3)*((6*x(t)^2+3*z(t)+1)*y(t)-(2*(1-y(t)^2))*x(t))*T(t)-(1-y(t)^2)*(Q(t)-(2/3)*P(t)) = 0;   

eq9 := diff(Z(t), t) = Z(t)*y(t);
syst := eq1, eq2, eq3, eq4, eq5, eq6, eq7, eq8, eq9;
ics := x(0) = .1, y(0) = .9, z(0) = .1, s(0) = .2, Q(0) = .1, P(0) = .9, R(0) = .1, T(0) = .2,  Z(0)=1;
sol1 := dsolve({ics, syst}, {P(t), Q(t), R(t), T(t), s(t), x(t), y(t), z(t), Z(t)}, type = numeric, output = operator);
sol1(0.5);
plots:-odeplot(sol1, [[t, y(t)], [t,Z(t)]], t=0..1, title="y and Z");
plots:-odeplot(sol1, [Z(t), y(t)], t=0..1, title="y vs Z");

      

Take the origin at A. Then the area a(t) of the triangle ABC is the absolute value of the determinant of <B,C>, so a(t) = |m t + n|.

We have a(0) = 2, a(5) = 3, a(10) = ?.
a(0)=2 implies n=±2, and a(5)=3 implies 5m+n=±3 so, a(10) = |10m+n| = |-n±6| = |n±6| ∈ {4,8}.

restart;
A := t->[a,sA+vA*t]: B := t->[b,sB+vB*t]: C := t->[c,sC+vC*t]:
area:= t->abs(LinearAlgebra:-Determinant(Matrix([[A(t)[],1],[B(t)[],1],[C(t)[],1]])))/2:
sols := solve([area(0)=2, area(5)=3, area(10)=AREA]):
AREA in {seq}( eval(AREA, sol), sol=sols);

                AREA  ∈  {4, 8}

(so, 2 solutions, AREA=4 and AREA=8).
Nice problem BTW.

p:=unapply(LinearAlgebra:-CharacteristicPolynomial(A,x), x):
[seq]( simplify(p(evstheory[i])), i=1 .. L^2); nops(%);

        [0, 0, ... , 0]
        81

but very SLOW!

Just the limit (it can be obtained at once).
Let A,B,C be consecutive vertices and M,N the midpoints of AB, BC.
For n --> oo, angle(ABC) --> Pi, so AC --> 2AB = 2 and MN = AC /2 --> 1.

Nice problem.

Conside the cube having lattice vertices  (x,y,z), with x,y,z in {0,1}.
We decompose the cube in six pyramids having a vertex in P(a,b,c) 
and the bases formed by the faces of the cube.
Denote by d1,...,d6 the distances from P to the six faces.
Then d1 + ... + d6 = 1+1+1 = 3 and
d1/1 = d2/3 = ... = d6/6 = (d1+ ... +d6)/(1+ ... +6) = 3/21 = 1/7.
So, {d1,...,d6} = {1/7, 2/7, 3/7, 4/7, 5/7, 6/7}.
Then the desired vertex is P(1/7,2/7,3/7}  
(because (1-1/7, 1-2/7, 1-3/7}= {4/7, 5/7, 6/7}).

P.S. All your proposed problems are nice but not very suitable to be solved
with Maple. Nice problems for a CAS can be found in:

Eilers S., Johansen R. - Introduction to Experimental Mathematics. CUP, 2017.

x*t is not a subexpression (operand of any level) in L. Use:

algsubs(x*t = Y, L)

 

dsolve( diff(y(x),x) = (x+y(x))/(y(x) - 3));

      -(1/2)*ln(-((x+3)^2-(x+3)*(3-y(x))-(3-y(x))^2)/(x+3)^2)-(1/5)*sqrt(5)*arctanh((9-2*y(x)+x)*sqrt(5)/(5*(x+3)))-ln(x+3)-_C1 = 0

You may append explicit, for an explicit solution.

1 2 3 4 5 6 7 Last Page 1 of 118